Temporal evolution of near‐surface chlorophyll over cyclonic eddy lifecycles in the southeastern Pacific. Issue 8 (1st August 2017) - Huang, Jie; Xu, Fanghua; Zhou, Kuanbo; Xiu, Peng; Lin, Yanluan
Abstract: Temporal evolution of near‐surface chlorophyll (CHL) associated with mesoscale eddies over entire eddy lifespan is complicated. Based on satellite measurements and a reanalysis data set, we identify and quantify major temporal and spatial CHL responses in cyclonic eddies in the southeastern Pacific, and explore the associated mechanisms. Only few temporal CHL variations can be directly linked to the four primary mechanisms: "eddy pumping, " "eddy trapping, " "eddy stirring, " and "eddy‐induced Ekman pumping." About 80% of the temporal CHL variations are too complex to be explained by a single mechanism. Five characteristic CHL responses, including classic dipoles (CD), positive‐dominant dipoles (PD), negative‐dominant dipoles (ND), positive monopoles (PM), and negative monopoles (NM) are identified using the self‐organizing map (SOM). CD, a dominant response induced primarily by "eddy stirring, " has a continued increasing of frequency of occurrence with time, although its contribution to the total CHL variability remains low. As the secondary prominent response, NM has two peaks of frequency of occurrence at eddy formation and maturation stages, mainly accounted by "eddy trapping" after eddy breakup and "eddy‐induced Ekman pumping, " respectively. The sum of frequency of occurrence of PD and PM are comparable to that of NM. The initial positive CHL at eddy formation stage is associated with "eddy trapping." The significant positive CHL increase from the eddy intensification to early decay stage is mainly attributed to "eddy pumping." Although the frequency of occurrence of ND is the smallest, its contribution to negative CHL anomalies is unnegligible. Key Points: About 80% of temporal CHL variations in eddies are linked to interplay of various physical mechanisms Five characteristic CHL responses are extracted based on the SOM Temporal CHL changes associated with the evolution of eddies are quantified for the five characteristic CHL responses